Reform of Higher Education Curriculum of Vocational Accounting Studies Based on SNDIKTI - Aulia, S; Anggraini, B D; Yukihana, A (KnE Social Sciences, 2018)
This study examined reform of higher education curriculum of vocational accounting studies based on the Standard of National Education. This study used literature review and a questionnaire by combining quantitative and qualitative research methods. This study only evaluates the implementation in the first-year curriculum in 2016. It found significant changes in the previous curriculum. The application of curriculum 2016 for the 1st year run effectively and increase of the understanding of the theory (knowledge) and technical ability (skill) as measured through assessment courses. Keywords: curriculum, theory, practice